A macro policy for poverty eradication through structural change - Rehman Sobhan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper argues that poverty originates in the structural injustices of a social order which incapacitates the poor from participating in the growth generating sectors of the economy and leaves them captives in the so called informal sector, characterized by low productivity and low earning capacity. In such a system the poor remain individualized and hence disempowered which compels them to interface with the market economy on highly inequitable terms which relegates them to the lowest tiers of the value addition chain. The need for a macro-policy designed to eliminate poverty is premised on the argument that poverty originates in the structural features of society which can only be addressed at the macro-level. Policy interventions, to redesign the structural sources of poverty, bring into consideration issues of social, political as well as economic reform.
Keywords: D02; E26; J54; O11; Q15; 330; Bangladesh; cooperatives; institutions; land; micro-credit; women; Armut; Sozialstruktur; Genossenschaft; Bangladesch; Mikrofinanz